Prevalence of mental health problems among university students and association with body mass index (BMI) and diet quality - Khairul Azhar, Nur Nadhira; Ibrahim, Muhamad Ariff; A Halim, Mohd Radzi Tarmizi; Shamsuddin, Aida Soraya; Azahari, Nuraniza; A. Malek, Mohd Ahsani (Faculty of Medicine and Health Sciences, UPM, 2023)
Introduction: Numerous factors contributed to the susceptibility of university students to develop mental health issues. Objective: This study aimed to assess the prevalence of mental health problems among International Islamic University Malaysia (IIUM) students and their relationships with diet quality and body mass index (BMI). Methods: A cross-sectional study was conducted among 104 students. The Depression, Anxiety, and Stress Scale (DASS-21) was used to assess students’ depression, anxiety, and stress levels. The Malaysian Healthy Eating Index (M-HEI) was used to assess diet quality. Spearman Rho was used to determine the relationships between variables. Results: Approx- imately 69.4% (n = 34), 71.4% (n = 35), and 48.9% (n = 34) of male students experienced moderate to extremely severe symptoms of depression, anxiety, and stress, respectively. In contrast, 85.4% (n = 47), 89.1% (n = 49), and 54.6% (n = 30) of female students had moderate to extremely severe symptoms of depression, anxiety, and stress, respectively. No correlations were found between diet quality and BMI with students’ mental health problems. For male students, there were negative significant associations reported between fat-rich foods (r = -0.447, p-value = 0.001) and sugar-rich foods (r = -0.332, p-value = 0.020) intake with depression; a positive significant relationship between fruit intake and anxiety (r = 0.284, p-value = 0.048); a positive relationship between fruit intake and stress (r = 0.300, p-value = 0.036); and a negative relationship between fat-rich foods and stress (r = -0.293, p-value = 0.041). Female students only had a significant negative correlation between fish intake and anxiety (r = -0.376, p-value = 0.005). Conclusion: No associations were found between diet quality, BMI, and mental health problems. A more profound comprehension of the connections between risk factors and mental health could lead to new intervention strategies.